Рівень чинника некрозу пухлин альфа і його кореляційні взаємозв'язки у хворих на цукровий діабет 2-го типу з неалкогольною жировою хворобою печінки - Михальчишин, Г. П.; Боднар, П. М.; Кобиляк, Н. М. (Clinical Endocrinology and Endocrine Surgery, 2014)
The article describes changes in serum levels of TNF-α and defines its associative relationships with anthropometric parameters and metabolic profile in patients with type 2 diabetes based on the presence NAFLD. According to our results the concentration of TNF-α in serum was statistically significantly higher in patients with NAFLD compared with the control group. In patients with NAFLD and normal transaminase levels TNF-α was higher on 45.5% (p=0,01) and 137,7% respectively (p<0,001) in patients with elevated transaminases compared to control group, in which the average cytokine serum concentration was 33,45±1,91 pg/ml. In all groups independent determinants associated with TNF-α in regression analysis were obesity and IR. In patients with NAFLD and normal range of liver enzymes compared to the control group showed an association with HDL-C and TG levels, and in the group with elevated transaminases also with ALT and AST.